2014
DOI: 10.1088/1742-6596/514/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical properties of very thin chromium films for optoelectronic devices

Abstract: Abstract. Establishing the optimal experimental conditions for the development of transparent metal contacts to be used in optoelectronic devices, such as organic light-emitting diodes and solar cells, is an important task. In this paper we present an overview of the development of very thin e-beam-deposited chromium films with high optical transparency. The surface morphology is investigated by scanning electron microscopy. The variation is examined of the films' electrical and optical properties (transmittan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Values for heat capacities obtained from fitting are within the expected range: the ratio between the lattice and electronic heat capacities during the excitation ( ~ 7) is comparable to that extracted from previous experiments 29 (larger values than in bulk 35 can be explained by disorder in the film 39 ), as is the value of thermal coupling constant k 35 . Absorption at 800 nm wavelength and 30° angle can be estimated based on measured complex refraction index for Cr thin films 40 as ~20%, while the obtained value of gives absorption of , which is remarkably close considering possible differences due to film roughness. With these fitted parameters, our theoretical model provides an excellent quantitative agreement with the experiment, as Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Values for heat capacities obtained from fitting are within the expected range: the ratio between the lattice and electronic heat capacities during the excitation ( ~ 7) is comparable to that extracted from previous experiments 29 (larger values than in bulk 35 can be explained by disorder in the film 39 ), as is the value of thermal coupling constant k 35 . Absorption at 800 nm wavelength and 30° angle can be estimated based on measured complex refraction index for Cr thin films 40 as ~20%, while the obtained value of gives absorption of , which is remarkably close considering possible differences due to film roughness. With these fitted parameters, our theoretical model provides an excellent quantitative agreement with the experiment, as Fig.…”
Section: Resultsmentioning
confidence: 75%
“…This is consistent with our electrical resistivity measurement reported here. An increase in the RF Lozanova et al [38] have previously examined the optical and electrical properties of chromium thin films of thickness values 5nm -100 nm prepared by electron beam technique.…”
Section: Sheet Resistance and Resistivity Of Chromium Oxide Filmsmentioning
confidence: 99%
“…The low resistivity value and high optical transmittance exhibited by the thin films prepared at lower deposition powers (e.g. sample prepared at 300W/10sccm) makes the film a promising transparent conducting oxide (TCO) for optoelectronic devices and other similar applications [38,41].…”
Section: Sheet Resistance and Resistivity Of Chromium Oxide Filmsmentioning
confidence: 99%
“…The Fresnel reflection coefficient, rpq, at the interface of two media, p and q, for perpendicularly incident light is a function of the refractive indices of the two media, np and nq: At wavelength λ1, the refractive indices of chromium and glass are around 3.5 [41] and 1.5, respectively, so R is approximately 78 %, which suggests that even if the chromium is transparent, the reflectivity is relatively high. For very thin layers, it has been shown that chromium does demonstrate transparency (e.g., about 50 % transmittance with a wavelength around λ1 for an 18 nm chromium layer [42]), but thicker coatings of chromium have demonstrated zero transmittance. For instance, Rauf et al [43] found zero transmittance in the wavelength range of 300 nm to 700 nm for a chromium layer thickness of 200 nm, and Wang et al [44] found zero transmittance at a wavelength of 550 nm for chromium layer thicknesses ≥ 100 nm.…”
Section: Uncertainty In Dhm Phase Measurementsmentioning
confidence: 99%